Pengembangan Potensi Ekonomi Masyarakat Desa Mojojajar - Dadang Purwo Ariwidodo; Rizki Nugianto; Moh. Ansori; Dines Olivia Margareta; Virlia Nanda Ristia; Achmad Rhodianto; Agit Bagus Dermawan; Mohammad Adifa Betha Nanda; Desinta Dwiki Nurfauziah; Kurnia Halimatus Solikhah; Roza Febrianti; Ineke Kusuma Indriani; Anggun Septiani Widorini; Devangga Dio Putra Arifin; Rizki Praham Sutarno; Nindy Pramudita; Suprayitno Suprayitno; Via Fitri Permatasari; Falaq Ikhzal Suganda; Retno Indah Pangestuti; Nova Kurnia Rahmadani; Naufal Anis Mubarok (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
This study presents the results of a survey conducted to analyze the impact of packaging training on the home industry of Samiler crackers in Mojojajar Village. A questionnaire was distributed to 25 respondents, including both consumers and producers of Samiler crackers. The findings reveal that 100% of respondents have purchased Samiler crackers, with 50% indicating that packaging is very important in their purchasing decisions. Additionally, 83.3% of respondents are willing to pay more for better packaging, highlighting the awareness of the importance of packaging quality. While many respondents find the current packaging design attractive, there is a need for improved information provided on the packaging. Recommendations for further development include enhancing packaging design, increasing awareness of government support for SMEs, and providing ongoing training on packaging techniques. This initiative is expected to contribute to local economic development and improve the welfare of the Mojojajar community.